2009
DOI: 10.1007/s10750-009-9786-9
|View full text |Cite
|
Sign up to set email alerts
|

Testing the enemy release hypothesis: trematode parasites in the non-indigenous Manila clam Ruditapes philippinarum

Abstract: The present study tested the 'Enemy Release Hypothesis' (ERH) which states that the success of an introduced species is related to the scarcity of natural enemies in the introduced range compared with the native range. Digeneans are dominant macroparasites of molluscs; therefore, the interaction between R. philippinarum and these parasites was ideal for investigation. A two-year monitoring in Arcachon Bay (SW France) was performed to estimate digenean loads in R. philippinarum and in three infaunal native biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…Clams from Arguin resisted better to trematode experimental infestation compared to those from Andernos. One possible explanation is that throughout their lifetime, clams from Arguin experienced an environment with a higher abundance of cercariae compared to what is shown at Andernos (Dang et al 2009a;Desclaux 2003). Similar local adaptation was also highlighted in populations used to experience trematode parasite infestation compared to populations without prior exposures (Bryan-Walker et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Clams from Arguin resisted better to trematode experimental infestation compared to those from Andernos. One possible explanation is that throughout their lifetime, clams from Arguin experienced an environment with a higher abundance of cercariae compared to what is shown at Andernos (Dang et al 2009a;Desclaux 2003). Similar local adaptation was also highlighted in populations used to experience trematode parasite infestation compared to populations without prior exposures (Bryan-Walker et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The bodies of water at both sites are sufficiently remote to exhibit different physical parameters, like temperature and salinity (Dang 2009), different benthic communities (Blanchet et al 2005), or planktonic assemblages (Glé 2007). It was also demonstrated that clams from Arguin and Andernos fed on different trophic sources (Dang et al 2009b) and that they were infested, like their surrounding cockles (C. edule), by different parasite propagules (Dang et al 2009a). Consequently, we presume that our adult individuals from Arguin and Andernos spent their lifetime (38 mm corresponds to an age of 3.4 years; Dang 2009) under different stressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a co-evolutionary history may often render invasive species non-competent hosts and thus acquisition of native parasite species may not take place. For example, the invasive Manila clam (Ruditapes phillipinarum) could not be artificially infected with the native trematode Himasthla elongata, while in the native common cockle (Cerastoderma edule) infection success was high (Dang et al, 2009). Free-living infective stages of the parasite were not able to infiltrate the epithelium of the invasive bivalve and thereby the low infections in the lab and the field resulted from a host (tissue) barrier (Dang et al, 2009).…”
Section: Parasite Release or Reductionmentioning
confidence: 99%